The relationship between ESG and firm value. Case study of the automotive industry - Dincă, Marius Sorin; Vezeteu, Cosmin-Dănuț; Dincă, Dragoș (Frontiers in Environmental Science, 2022)
The automotive industry is set to face a series of fundamental changes in the following years. Along with the transition to electric vehicles or production of autonomous cars, companies are also expected to better address sustainability issues, usually divided into environmental, social and governance (ESG) aspects. The present paper aims to explore the relationship between non-financial sustainability, measured by ESG scores, and firm value in the automotive industry, where empirical evidence is scarce. A structural equation modelling (SEM) approach has been taken on a novel dataset of 131 listed companies worldwide across 6 years. Our results indicate a mixed influence of the E, S, G scores on firm value in the analyzed period, with some inconclusive effects, especially from the social score. The findings are beneficial for investors, fund managers and automotive companies’ executives. Further research directions are also provided.